Book Review - Medicinal Value of Indian Spices, AMIT KRISHNA DE (Editor) - CHEMPAKAM, B (Journal of Spices and Aromatic Crops, 1998)
The book provides a general account of the medicinal values of various Indian spices. The first part of the book is divided into six chapters, each chapter depicting the role of various spices in therapeutics. The second part describes aspects on cultivation, production, processing and quality control in spices. Most of the chapters in the book are papers presented at the National Symposium on Medicinal Values of Indian Spices, held at Calcutta in 1993, as mentioned in the preface.